2009
DOI: 10.1128/cvi.00254-09
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Genes in Toll-Like Receptor-Mediated Signaling of Broilers Infected with Clostridium perfringens

Abstract: Toll-like receptors (TLRs) participate in detecting microbial pattern molecules for activation of the host immune response. We investigated possible roles of TLRs in the chicken response to Clostridium perfringens infection by examining the expression of TLR genes and other genes involved in TLR-mediated signaling within the spleens and ilea of C. perfringens-challenged broilers. Upregulation of a tumor necrosis factor alphainducing factor homolog in challenged chickens compared to naïve chickens was observed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 43 publications
3
38
0
2
Order By: Relevance
“…Therefore, the inclusion of MOS to broiler chickens might have a beneficial property on innate immune system function in the ileum of birds. The findings in the current study in the COC group are in agreement with the report from Lu et al (2009), where they showed no significant up/downregulation in TLR2 and TLR4 expressions in the ileum of birds challenged with C. perfringens 4 d postchallenge. However, there was a higher expression of TLR4 in both the ileum and cecal tonsil in MOSC treatment in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the inclusion of MOS to broiler chickens might have a beneficial property on innate immune system function in the ileum of birds. The findings in the current study in the COC group are in agreement with the report from Lu et al (2009), where they showed no significant up/downregulation in TLR2 and TLR4 expressions in the ileum of birds challenged with C. perfringens 4 d postchallenge. However, there was a higher expression of TLR4 in both the ileum and cecal tonsil in MOSC treatment in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Variation in immune response during the course of infection is attributed to the difference in disease susceptibility (Zekarias et al 2002). The TLR4 expression is up regulated in spleen of chickens challenged with Clostridium perfringens and S. enteritidis (Lu et al 2009, Abasht et al 2009). Moreover, TLR4 mRNA is differentially expressed in caecal tonsils of Salmonella-resistant and -susceptible lines of laying hens (Sadeyen et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Given that Toll-like receptors (TLR) participate in pathogen detection and activate innate immune responses, Lu et al (2009) investigated the expression levels of chicken TLR after infection with C. perfringens. In summary, TLR1 type 1 levels in the spleen were upregulated at 1 d postinfection, whereas in the intestine, the levels were increased at d 2.…”
Section: Cytokine and Toll-like Receptor Expressionmentioning
confidence: 99%